2016
DOI: 10.1262/jrd.2015-095
|View full text |Cite
|
Sign up to set email alerts
|

The efficiency of vaginal temperature measurement for detection of estrus in Japanese Black cows

Abstract: Recently, weak estrous behavior was assumed to be the cause of a decline in breeding efficiency in cattle. The present study investigated the effect of measuring the vaginal temperature on the detection of estrus in Japanese Black cows. First, the effect of hormone administration to cows with a functional corpus luteum on the vaginal temperature was evaluated by continuous measurement using a temperature data logger. After 24 h of cloprostenol (PG) treatment, the vaginal temperature was significantly lower tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
34
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 40 publications
6
34
0
7
Order By: Relevance
“…However, during this extensive field study, heat stress was not found to have an effect on CRFA or CFAI, with CFAI tending to be longer during the cold season. Sakatani et al (2012) previously showed that heat stress did not have as strong an effect on rectal temperature in Japanese Black cattle than in certain dairy cows, such as Holstein Friesian, indicating that beef cattle are a thermotolerant breed (Sakatani, Takahashi, & Takenouchi, 2016).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, during this extensive field study, heat stress was not found to have an effect on CRFA or CFAI, with CFAI tending to be longer during the cold season. Sakatani et al (2012) previously showed that heat stress did not have as strong an effect on rectal temperature in Japanese Black cattle than in certain dairy cows, such as Holstein Friesian, indicating that beef cattle are a thermotolerant breed (Sakatani, Takahashi, & Takenouchi, 2016).…”
Section: Discussionmentioning
confidence: 97%
“…Sakatani et al. () previously showed that heat stress did not have as strong an effect on rectal temperature in Japanese Black cattle than in certain dairy cows, such as Holstein Friesian, indicating that beef cattle are a thermotolerant breed (Sakatani, Takahashi, & Takenouchi, ). Thus, Japanese Black cattle appear to be more susceptible to the cold than to heat.…”
Section: Discussionmentioning
confidence: 99%
“…To calculate the estrus duration, the beginning of estrus (0 hr) was determined when the numbers of steps (/hr) became 1.5‐fold higher than the 14‐day average before estrus (steps/hr) and remained at this higher level for more than 3 hr (Sakatani, Balboula, Yamanaka, & Takahashi, ; Sakatani et al., ; Yoshioka et al., ). The end of estrus was defined as the time when the steps/hr returned to less than 1.5 times the 14‐day average level.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the detection of estrus by the measurement of steps is suitable from the standpoint of labor reduction and animal welfare. However, in some situations, such as in tiestalls or during the summer season, the activity and number of steps during estrus are difficult to detect, and so the effectiveness of detecting estrus by pedometer is limited (Sakatani, Takahashi, & Takenouchi, ).…”
Section: Introductionmentioning
confidence: 99%
“…Pengukuran suhu vagina selama berahi telah dilaporkan bahwa peningkatan suhu tubuh berhubungan dengan hormon yang disekresikan selama berahi (Sakatani, Takahashi, and Takenouchi, 2016 …”
Section: Pengaruh Karakteristik Lendir Servik Terhadap Suhu Vaginaunclassified